(untitled) (Revista de Artes Marciales Asiáticas, 2012)
Iaido (fast drawing of the sword) and Ken Jutsu (saber fencing) are two Japanese martial arts that have overcome their pragmatic character to become spiritual ways of self-cultivation. In this essay, the author presents some of the keys and fundamental ideas that support this concept. From this perspective, the mysticism of both disciplines already starts at the very forging process of the sword and spreads to the last performance of the techniques, when the player is released from all that binds him to the world through the cutting gesture.